2013
DOI: 10.1152/japplphysiol.01271.2012
|View full text |Cite
|
Sign up to set email alerts
|

Evaporative cooling: effective latent heat of evaporation in relation to evaporation distance from the skin

Abstract: Havenith G, Bröde P, den Hartog E, Kuklane K, Holmer I, Rossi RM, Richards M, Farnworth B, Wang X. Evaporative cooling: effective latent heat of evaporation in relation to evaporation distance from the skin. J Appl Physiol 114: 778 -785, 2013. First published January 17, 2013 doi:10.1152/japplphysiol.01271.2012.-Calculation of evaporative heat loss is essential to heat balance calculations. Despite recognition that the value for latent heat of evaporation, used in these calculations, may not always reflect th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
108
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 111 publications
(110 citation statements)
references
References 23 publications
1
108
1
Order By: Relevance
“…Since Gagge's seminal work (1937), the measurement of w has received great attention, particularly in the context of predicting the body's heat balance during conditions of increased metabolic heat production (e.g., resulting from exercising muscles) and decreased gradient for heat loss to the environment (e.g., resulting from high ambient temperatures) (Candas et al 1979;Havenith 2001;Havenith et al 2013;Nadel and Stolwijk 1973). However, although much is known on the biophysical role of w in contributing to thermal homeostasis, surprisingly little has been done to elucidate how humans sense wetness on their skin and how the level of "physical" skin wetness relates to the level of "perceived" skin wetness (Montell 2008).…”
mentioning
confidence: 99%
“…Since Gagge's seminal work (1937), the measurement of w has received great attention, particularly in the context of predicting the body's heat balance during conditions of increased metabolic heat production (e.g., resulting from exercising muscles) and decreased gradient for heat loss to the environment (e.g., resulting from high ambient temperatures) (Candas et al 1979;Havenith 2001;Havenith et al 2013;Nadel and Stolwijk 1973). However, although much is known on the biophysical role of w in contributing to thermal homeostasis, surprisingly little has been done to elucidate how humans sense wetness on their skin and how the level of "physical" skin wetness relates to the level of "perceived" skin wetness (Montell 2008).…”
mentioning
confidence: 99%
“…Adapted from Hu et al 44 based on the wicking speed in-plane, through-plane and total moisture absorption. The MMT is also described by the AATCC test method 195-2009 4,9 and was used, for example, to evaluate knitted fabrics of bamboo yarns. 50 Wardinigsih and Troynikov 50 investigated bamboo fabrics with the MMT and found that the cover factor (i.e.…”
Section: Electrical Impedancementioning
confidence: 99%
“…In sports, the reduced cooling efficiency of sweat may increase the risk of heat stress. 4 Perspiration that is not taken up and wicked by the multi-layer protective garments of firefighters and thus left on the skin can lead to steam burns. 5 Wet textiles in contact with the skin have a higher friction coefficient and can cause blisters 6,7 and decubitus in immobile patients.…”
mentioning
confidence: 99%
“…The overall cooling effects of sweat evaporation for clothed persons has been carried out on human subjects as well as using thermal manikins [3][4][5][6]. However, the outcomes have been difficult to related to clothing design and fabric selection because the data are confounded by heat loss due to the latent heat of vaporization which cannot be assessed separately [7]. The cooling generated by wet clothing, independent of body metabolic heat loss, and the associated latent heat of vaporization, have not been separated.…”
Section: Introductionmentioning
confidence: 99%